Toxic Effects of Chronic Mercury Exposure on the Retinal Nerve Fiber Layer and Macular and Choroidal Thickness in Industrial Mercury Battery Workers - Ekinci, Metin (International Scientific Literature, Inc., 2014)
BACKGROUND: The aim of this study was to evaluate the toxic effects of mercury on retinal nerve fiber layer thickness (RNFLT), macular thickness (MT), and choroidal thickness (CT) by using spectral-domain optical coherence tomography (SD-OCT) in battery industry workers who had been chronically exposed to mercury. MATERIAL/METHODS: Battery factory workers (n=31) and healthy non-factory employee controls (n=15) participated in the study. Participants were divided into 3 groups: Group 1 (n=15) was factory workers who had worked for more than 5 years in a mercury battery factory; Group 2 (n=16) was factory worker who had worked for less than 5 years in a mercury battery factory; and Group 3 (n=15) was healthy non-employees. Systemic symptoms were recorded. Ophthalmic examination included best-corrected visual acuity test, color vision test, full ophthalmologic examination, and SD-OCT of the RNLF, macula, and choroid. To determine mercury exposure, venous blood samples were collected and mercury levels were assessed. RESULTS: In our study group the most common systemic symptoms were insomnia (67.7%) and fatigue (67.7%). There were no significant differences between Group 1 and Group 2, but there were significant differences between Group 3 and both Group 1 and Group 2 in best-corrected visual acuity values (1=2<3), color vision scores, blood mercury levels, and duration (mean ±SD, range) of mercury exposure(1>2>3). OCT values of RNFLTs, MTs, and CTs of all 3 groups were statistically different from each another (1<2<3). CONCLUSIONS: SD-OCT can be useful for evaluating the toxic effects of chronic exposure to mercury.